Asymptomatic Spinal Cord Compression: Is Surgery Necessary to Return to Play. Issue 5 (11th January 2021) - Lee, Yunsoo; Selverian, Stephen; Hsu, Wellington K; Watkins, Robert G; Vaccaro, Alexander R; Hecht, Andrew C
Abstract: Advising athletes with asymptomatic cervical canal stenosis on their return to active play is a topic of considerable debate, with no definitive guidelines in place. Once cervical canal stenosis is identified, often through imaging following other injuries, it is difficult to predict the risk of future injury upon return to play in both contact and collision sports. Consequently, the decision can be a complicated one for the athlete, family, and physician alike. In this article, we identify radiographical and magnetic resonance imaging (MRI)-based criteria that may distinguish athletes "at-risk" for more severe consequences due to asymptomatic cervical canal stenosis from those who are safe to return to play. Using a Torg-Pavlov ratio <0.7 and MRI metrics, namely a minimal disc-level canal diameter <8 mm, a cord-to-canal area ratio >0.8, or space available for the cord <1.2 mm, can help when making these difficult decisions. Counseling can be a critical asset to patients with cervical stenosis who have had a previous episode of cervical cord neuropraxia, especially when they are involved in high-risk sports such as American football and rugby. We believe that while this remains an area of continued concern and controversy, improved MRI criteria will be a useful springboard for further studies, especially in the elite athlete population.